The Existence and Durability of Pesantren during the Covid-19 Pandemic - Moh Ashif Fuadi (Dialogia: Islamic Studies and Social Journal, 2021)
The Covid-19 pandemic affects all elements of life. The impact is very felt not only on the economy and health but also has an impact on activities in pesantren. Islamic Boarding school becomes a crater candradimuka to educate students who learn religious science through the education of kiai. The five basic elements of pesantren, namely kiai, santri, dormitory, mosque, and yellow book, become a tree that should not be left behind. This research informs us about the existence of pesantren in efforts to mitigate the COVID-19 pandemic as well as its durability for the continuity of activities in pesantren by collecting previous research, relevant research libraries, news, or information related to handling pandemics in pesantren through online media. Then with the approach of structural functionalism, Talcott Parsons AGIL (adaptation, goal attainment, integration, latency) where social stem everywhere including pesantren is always related to interrelated elements so that pesantren will have endurance in carrying out its functions. The result of this research is that pandemics greatly impact the activities of pesantren typical with calves and culture. Various mitigations have also been done to prevent pesantren clusters, and through the AGIL approach, pesantren will be more responsive in dealing with the Covid-19 pandemic.Pandemi COVID-19 berdampak kepada seluruh elemen kehidupan. Dampak yang dirasa bukan hanya pada sektor ekonomi dan kesehatan, namun juga dampak kegiatan pendidikan di pesantren. Tempat tersebut menjadi kawah candradimuka untuk mendidik para santri belajar ilmu agama melalui pendidikan seorang kiai. Lima elemen dasar pesantren yakni kiai, santri, asrama, masjid, dan kitab kuning menjadi pokok kesatuan dalam aktivitas pesantren. Penelitian ini membahas tentang upaya mitigasi dampak pandemi COVID-19 dan daya tahan keberlangsungan kegiatan di pesantren. Dengan mengumpulkan penelitian terdahulu library research yang relevan dan informasi penanganan pandemi di pesantren melalui media online serta mengaitkannya dengan pendekatan fungsionalisme struktural Talcott Parsons AGIL (adaptation, goal attainment, integration, latency) dimana sistem sosial selalu berkaitan dengan elemen-elemen yang saling berkaitan sehingga pesantren akan memiliki daya tahan dalam menjalankan fungsinya. Hasil dari penelitian ini adalah dampak pandemi di pesantren menyebabkan beberapa langkah mitigasi melalui penerapan protokol kesehatan diterapkan dengan level yang berbeda-beda untuk mencegah klaster pesantren. Selain itu terdapat tiga saluran masuknya virus COVID-19 yang potensial terjadi pesantren dan melalui pendekatan AGIL, pesantren bisa lebih tanggap dalam menghadapi pandemi COVID-19.